Perancangan Sitem Uji Kebergunaan Aplikasi Berbasis Web Menggunakan System Usability Scale - Muis Nanja; Yulianti Lasena; Hastuti Dalai (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2022)
Applications are software in the form of programs, both as desktop applications, web and mobile applications that are built to assist in work or various human activities. The number of mobile application competitions between Gojek, Maxim, Grab, Nujek and so on. It is deemed necessary to test the usability value of the application in order to see the level of user convenience and comfort based on the experience of using the application. The results of developing web-based applications using SUS can be seen from the results of tests carried out on application programs built using white box testing and black box testing. The results obtained from the white box test, namely the (CC) test, obtained the value of V(G) = E – N + 2=2 and V(G)= P + 1 = 2, meaning that the results obtained are valid because of the suitability of the region value with the CC calculation results. The results of the black box test have given the results as expected, then the calculation (SUS) obtained an average value of 72 which means the application is in the good category.